Effects of Cow Dung Ash on Chemical and Geotechnical Properties of Lateritic Soil for Road Construction collected Shao-Malete Road in Kwara State, Nigeria - A. G. Adelodun; O. O. Amu; K. J. Ayinde (Journal of Applied Sciences and Environmental Management)
The objective of this paper was to investigate the effects of cow dung ash (CDA) on the chemical and geotechnical properties of lateritic soil for road construction collected Shao-Malete Road in Kwara State, Nigeria. Cow dung ash (CDA) was used in stabilizing lateritic soil at ratios 0, 2, 4, 6, 8 and 10% of disturbed soil sample (fine - grained i.e. silt-clay material). The soil samples were subjected to laboratory tests such as Specific gravity, particle size distribution, Atterberg limits, compaction, California bearing ratio, unconfined compressive strength, Triaxial shear strength in accordance with British Standards (BS 1377: 1990 and BS 1924: 1990). Optimum addition of cow dung ash was achieved at 6%. The investigation on the soil samples revealed an increased in strength tests performed on the selected soil samples and a gradual decrease in the results of optimum moisture content. Optimum of CDA was recorded at 6% which is best suitable for silt-clay soil. In conclusion, materials from selected locations meet the requirements for sub-base and base courses when stabilized with optimum cow dung ash. If the research work is utilized for road and building construction, it will surely cut down expenses and environmental risks brought about by agricultural waste.